Computing Vessel Velocity from Single Perspective Projection Images - Huillca, Jose Luis; Fernandes, Leandro A. F. (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2021: Anais Estendidos da XXXIV Conference on Graphics, Patterns and ImagesDO - 10.5753/sibgrapi.est.2021.20017, 2021)
The Master’s Thesis presented an image-based approach to estimate the speed of moving vessels from their traces on the water surface. Vessels moving at constant heading and speed display a familiar V-shaped pattern which only differs from one to another by the wavelength of their transverse and divergent components. Such wavelength is related to vessel speed. We use planar homography and natural constraints on the geometry of ships’ wake troughs to compute vessel speed from single optical images acquired by conventional cameras. Experiments show that our approach produces compelling results, which are in accordance with true data available for the observed vessels.